The emotional education as a bridge to harmonization in school practice in Early Childhood Education (Research, Society and Development, 2020)
This article aims to establish a bridge of harmonization between Emotional Education and Early Childhood Education, regarding the understanding of emotions and feelings in teaching learning. It refers to an explanatory and qualitative research, executed in the classroom practice experience in a foreign school in the city of João Pessoa (Paraíba). The theory presented in this research was based on the theoreticians Daniel Goleman, as well as Howard Gardner, with his Multiple Intelligences theory, Peter Salovey and David Sluter in his book "Emotional Intelligence of the Child". The results presented indicate that children at this age do not reach their emotions and therefore certify with outrageous behavior. However, teachers of early childhood education can provide alternatives in the school environment to help children understand with their emotions and experience challenges, enabling them to make their own decisions. When children know how to distinguish their emotions and know how to differentiate them, they open paths for teaching learning in the classroom. In this way, the teacher, transmitter of knowledge, exposes the harmonization through resources in the school environment, acting in this way in their classroom routine, bringing necessary benefits in the construction of the child as an integral being.